Application Block’s table in the study of recreational and geographical disciplines - Бейдик, О. (Київський національний університет імені Тараса Шевченка, 2016)
A number adapted to the geography (recreational resource component, a UNESCO World Heritage Site, UNESCO World Heritage and the “Seven Wonders” of Ukraine) Block’s tables and reasonable possibility of their use in geographical, historical, structural and geographical, geographic and tourist historical and archaeological disciplines. The use of active learning methods, including adapted to the geographical perspective Block’s tables, promotes concentration, development, training of attention and thinking (individual and group) and supports the objective perception of natural factors, socio-political, economic phenomena and processes. A Block 25 version of the table in the regions of Ukraine and seven tourist-geographical macro-regions of World (version are integrated systematization World Heritage World), which act reference links and recreational resource framework of Ukraine and the world. Technology use spreadsheets unit can be used as a classical geographic (economic and social geography, physical geography of continents and oceans, local history, geography, world economy) and structural and geographical (market activity of tourist businesses, recreational facilities, recreational and tourist resources, geography tourism) disciplines. Use tables Schulte was a definite step in the development of psycho-pedagogical and mnemonics technologies used in geography. Application Block’s table in geographic disciplines considered as part of the trend outlined above. The proposed table of American psychologist John Block your time compared with thermometers. Although it does not measure the temperature, and the person’s attention, the primary task she had a, like a thermometer: send a signal of danger. With a simple test to determine whether he is able, who will test to become a driver? The task of containing a table is a sequential search numbers from 10 to 59 (of 50 cells) at a fixed time. The best result is a search when each number of “takes” of 10-20 seconds. In addition, the analysis of strengths and weaknesses adaptation tables Block to the educational process, based on a realization of a number of educational experiments.

Запропоновано ряд адаптованих до географії (ресурсно-рекреаційна складова, об’єкти Всесвітньої спадщини ЮНЕСКО, об’єкти Всесвітнього надбання та “Сім чудес” України) таблиць Блока та обґрунтовано можливості їх застосування в географічних, історичних, конструктивно-географічних, туристсько-географічних та історико-археологічних дисциплінах. Застосування активних методів навчання, в т.ч. адаптованих до географічної проблематики таблиць Блока, сприяє концентрації, розвитку, тренуванню уваги та мислення (індивіда та групи) та виступає чинником об’єктивного сприйняття природних, суспільно-політичних, економічних явищ та процесів. Запропоновано 25 варіантів таблиць Блока в розрізі регіонів України та 7 туристсько-географічних макрорайонів світу (наведено інтегрований варіант систематизації об’єктів Всесвітньої спадщини світу), які виступають опорними ланками ресурсно-рекреаційного каркасу України та світу. Технологія використання таблиць Блока може бути застосована як до класичних географічних (економічна і соціальна географія, фізична географія материків і океанів, країнознавство, географія світового господарства), так і конструктивно-географічних (ринкова діяльність туристських підприємств, рекреаційні комплекси, рекреаційно-туристські ресурси, географія туризму) дисциплін. Використання таблиць Шульте було певним кроком у розвитку психолого-педагогічних та мнемотехнічних технологій, що застосовуються у географії. Застосування таблиці Блока в географічних дисциплінах розглядається, як складова окресленого вище тренду. Запропоновану таблицю американський психолог Дж. Блок свого часу порівнював з термометром. І хоча вона вимірює не температуру, а увагу людини, первинне завдання у неї було таке, як у градусника: надіслати сигнал про небезпеку. За допомогою простого тесту можна визначити, чи здатний той, кого випробують, стати водієм? Завдання, яке містить таблиця, полягає у послідовному пошуку чисел від 10 до 59 (всього 50 комірок) за фіксований час. Оптимальним результатом є такий пошук, коли кожне число “забирає” 10-20 секунд. Наведений аналіз сильних і слабких сторін адаптації таблиць Блока до навчального процесу, основою якого є реалізація ряду педагогічних експериментів.
Застосування таблиці Блока при вивченні рекреаційно-географічних дисциплін
Beydyk O. (2000) Dyversyfikatsiya tvorchoho pidkhodu do konstruyuvannya navchal’noho protsesu [Diversification creative approach to designing educational process]. Visnyk Kyyivs’koho instytutu «Slov”yans’kyy universytet». Ekonomika, Issue, 6, pp.23-29 [in Ukrainian] Beydyk O. (2005) Personal-tekhnolohiyi pidhotovky fakhivtsiv dlya turyst·s’ko-rekreatsiynoyi sfery [The staff technology training for tourism and recreation], Visnyk KNUKiM. Ser. Pedahohika , Issue 12, part. 1, pp. 47–50 [in Ukrainian] Beydyk A. (2006) Aktivnyye metody obucheniya v spetskursakh turistsko-rekreatsionnogo bloka [Active methods of training in special courses tourism and recreation unit], Kultura narodov Prichernomoria, No. 88, pp. 7-11 [in Russian] Beydyk O. ( 2007) Zastosuvannya aktyvnykh metodiv pry vykladanni rekreatsiyno-turystychnykh dystsyplin u vyshchykh navchal’nykh zakladakh [The use of active methods in teaching recreation and tourism subjects in higher education], Turystychno-krayeznavchi doslidzhennya, Issue 7, pp. 214-227 [in Ukrainian] Beydyk O. (2011) Zastosuvannya tablyts’ Shul’te pry vyvchenni rekreatsiyno-heohrafichnykh dystsyplin [Application Schulte tables in the study of recreational and geographical disciplines], Naukovyy chasopys NPU imeni M.P. Drahomanova. Seriya 4. Heohrafiya i suchasnist’, Issue 14 (26), pp.91-97 [in Ukrainian] Beydyk O., Novosad N.O. (2013) Unikal’na Ukrayina: heohrafiya ta resursy turyzmu: Navchal’nyy posibnyk [Unique Ukraine: geography and tourism resources: Manual], Kyiv : Al’terpres,572 p. [in Ukrainian] Beydyk O., I. Lazaruk (2015) Rekreatsiyno-turysts’ki resursy Mykolayivs’koyi oblasti v tablytsyakh Shul’te [Recreation and tourism resources of Mykolayiv region in the tables Schulte], Suchasni tendentsiyi rozvytku turyzmu : Zb. nauk. prats’, Mykolayiv : MF KNUKIM, pp. 16-21 [in Ukrainian] Beydyk O., Lazaruk I. (2016) Natsional’na ta svitova arkheolohiya v tablytsyakh Shul’te [National and world archeology in tables Schulte], Lyudyna ta landshaft: heohrafichnyy pidkhid v pervisniy arkheolohiyi : Mizhnarodn. nauk. konf.Kyiv : Starodavniy svit, 2016, p. 32 [in Ukrainian] Bondarchuk L. (1993) Metody aktyvnoho navchannya v kursi «Osnovy pedahohichnoyi maysternosti» [Methods of active learning in the course “Basics of pedagogical skills”], Vyshcha i serednya pedahohichna osvita, no. I6, pp. 51-56 [in Ukrainian] Burlachuk L. (2007) Slovar’-spravochnyk po psykhodyahnostyke[Dictionary of psychodiagnostics], Saint Petersburg: Pyter, 2007, pp. 341-343 [in Russian] Volod’ko V., Ivanova T. (1993) Samostiyna navchal’no-piznval’na diyal’nist’ yak odyn z metodiv rozvytku tvorchykh zdibnostey studentiv [Independent educational and cognitive activity as a method of creative abilities of students],Vyshcha i serednya pedahohichna osvita, no. I6,p. 62 [in Ukrainian] Zhukova R. Kuznetsov Yu. (1989) Aktyvnye metody obuchenyya v kontseptsyy perestroyky uchebnoho protsessa [Active methods of training in the concept of restructuring the educational process], Aktyvnye metody obuchenyya v systeme podhotovky spetsyalystov y rukovodyteley, Leningrad, pp. 5-13 [in Russian] Lozova V. (1989)Problema aktyvizatsiyi piznaval’noyi diyal’nosti studentiv pry vyvchenni psykholoho-pedahohichnykh dystsyplin [The problem of cognitive activity of students in the study of psychological and pedagogical subjects], Vyshcha i serednya pedahohichna osvita, no. 14, pp. 6Z-68 [in Ukrainian] Na tsepkyy shoferskyy hlaz(1975) [On tenacious driver’s eyes], Rovesnyk, no. 12, p. 22 [in Russian] Tarasov V. (1989) Personal-tekhnolohyya: otbor y podhotovka menedzherov [Personnel-technology: selection and training of managers], Leningrad. : Mashynostroenye, 175-185 [in Russian] Khudyk V. (1994) Psykholohycheskye metodyky yssledovanyya yntellekta y lychnosty: tablytsy Shul’te [Psychological methods of investigation of intelligence and personality: Schulte table], Kyiv: Zdorov’e, 20 p. [in Russian] Shchurkova N. (1998) Praktykum po pedahohycheskoy tekhnolohyy [Workshop on educational technology], Moscow, 1998, pp. 6-7 [in Russian] Svidotstvo pro reyestratsiyu avtors’koho prava na tvir no. 67838. Ukrayina. Naukova stattya «Zastosuvannya tablyts’ Shul’te pry vyvchenni heohrafichnykh ta istorychnykh dystsyplin» [Certificate of registration of copyright №67838. Ukraine. The scientific paper “Application Schulte tables in the study of geographical and historical subjects”],Beydyk O. (Ukraine), 15.09.2016 [in Ukrainian]
Keywords: опорні ланки ресурсно-рекреаційного каркасу; таблиці Блока; таблиці Шульте; об’єкти Всесвітнього надбання; активні методи навчання; переваги та недоліки адаптації таблиць до навчання; basic level of resource and recreational frame; Blok table; tables Schulte; World Heritage sites; active learning methods; advantages and disadvantages tables adaptation to training